Developing Workforce Capacity in Public Health Informatics: Core Competencies and Curriculum Design - Douglas R. Wholey; Martin LaVenture; Sripriya Rajamani; Rob Kreiger; Craig Hedberg; Cynthia Kenyon (Frontiers Media S.A., 2018)
We describe a master's level public health informatics (PHI) curriculum to support workforce development. Public health decision-making requires intensive information management to organize responses to health threats and develop effective health education and promotion. PHI competencies prepare the public health workforce to design and implement these information systems. The objective for a Master's and Certificate in PHI is to prepare public health informaticians with the competencies to work collaboratively with colleagues in public health and other health professions to design and develop information systems that support population health improvement. The PHI competencies are drawn from computer, information, and organizational sciences. A curriculum is proposed to deliver the competencies and result of a pilot PHI program is presented. Since the public health workforce needs to use information technology effectively to improve population health, it is essential for public health academic institutions to develop and implement PHI workforce training programs.